UPAYA PENINGKATAN PEMBELAJARAN LOMPAT JAUH DENGAN PERMAINAN LOMPAT KIJANG UNTUK SISWA KELAS V SD NEGERI 12 JAMBU (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Model of Research of class action ( PTK) with aim to look for the trouble-shooting practically orienting at action. Where each;every cycle consisted of by 4 phase that is (1) planning phase, (2) action Phase, (3) observation Phase, (4) phase refleksi to form of game of long jump (pass/through) to jump the deer to student of class of V of Elementary School of Country 12 Jambu. Research Method used by is (1) method of enquette of study expert, (2) enquette methodÂ  student. this Subyek Research that is entire/all student of class of V SD Country 12 Jambu of District Mlonggo amounting to 16 student. Technics analyse the data used by is descriptive of presentase to express the aspect psikomotoric, cognate, and afektif student. Result of research, at cycle I of data acquirement evaluate the assessment from expert study obtained by result 52,00 % (enough), cycle II obtained by result 72,00 % ( good), while at Cycle I of is percentage of answer of kuesioner student equal to 49,38 % ( enough), and Cycle II of is percentage of answer of kuesioner student equal to 81,33 % ( good). From inferential research result that study of athletic of long jump (pass/through) the game jump this deer can be used to student of class of V SD Country 12 Jambu of District of Mlonggo of Sub-Province Jepara with the good result.